2007
DOI: 10.1021/ja076281t
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Tomography of Cancer-Cell Spheroids Reveals Incomplete Uptake of Both Platinum(II) and Platinum(IV) Complexes

Abstract: The limited penetration of cytotoxic drugs into tumors is a significant contributing factor to the limited effectiveness of cancer chemotherapy. Here we have shown that X-ray fluorescence microtomography is a suitable technique for imaging the distribution of Pt drugs within multicellular tumor spheroids, models of solid tumors. This has revealed that there is no significant difference between the distributions of the range of Pt(II) and Pt(IV) complexes investigated, suggesting that complexes that are more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 20 publications
1
53
1
1
Order By: Relevance
“…12,89 A major cause of the limited efficacy of anticancer agents is believed to be multicellular resistance associated with poor penetration into regions of solid tumors more than 40-100 µM from the vasculature. 90 These isolated regions evolve as a result of tumor cells proliferating at a faster rate than the development of new blood vessels, and are characterized by oxygendeprivation (hypoxia) and low pH resulting from the buildup of metabolic products such as lactic acid and carbonic acid. 12,68,89 Chemotherapy is believed to encounter resistance from these regions due to the harsh conditions and the greater distance that drugs must diffuse from the vasculature to reach them.…”
Section: Multicellular In Vitro 3-d Tumor Modelsmentioning
confidence: 99%
“…12,89 A major cause of the limited efficacy of anticancer agents is believed to be multicellular resistance associated with poor penetration into regions of solid tumors more than 40-100 µM from the vasculature. 90 These isolated regions evolve as a result of tumor cells proliferating at a faster rate than the development of new blood vessels, and are characterized by oxygendeprivation (hypoxia) and low pH resulting from the buildup of metabolic products such as lactic acid and carbonic acid. 12,68,89 Chemotherapy is believed to encounter resistance from these regions due to the harsh conditions and the greater distance that drugs must diffuse from the vasculature to reach them.…”
Section: Multicellular In Vitro 3-d Tumor Modelsmentioning
confidence: 99%
“…[56] In addition, the study showed poorer but similar penetration profiles of Pt(IV) complexes in comparison to cisplatin and represents an interesting future mechanism for studying the efficiency of other anti-cancer agents. [56] While not a medicinal chemistry application, de Jonge and Vogt [57] have performed higher resolution imaging of the whole diatom, Cyclotella meneghiniana, with 150-nm voxels over a 15-µm field of view. An exciting prospect of the technique would be the incorporation of cryocapabilities which would enable the 3-D elemental analysis of frozenhydrated specimens.…”
Section: Nanoparticles and Nanoconjugatesmentioning
confidence: 82%
“…Microprobe SRXRF has proven itself as a technique for providing unequalled information regarding the distribution of metal and metalloid-containing drugs in cells and tumours at subtoxic and therapeutic doses. [8,26,[31][32]38,[40][41]56] Targets such as the nucleus, [26,38] including the euchromatin [32] and heterochromatin [8] regions, nucleoli, [32,48,52] membranes, and mitochondria [52] can be identified as sites of localisation following studies of existing and potential therapeutic and diagnostic agents. The technique has been invaluable for confirming theories of drug actions (namely, the coordinative action of cisplatin and its analogues) [38][39] and for confirming concepts associated with the modes of action of designed therapeutics (namely, confirmation of drug penetration to the site of dense DNA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations